Predictive factors for survival of patients with inoperable malignant distal biliary strictures: a practical management guideline. Issue 1 (1st January 1998) - Prat, F; Chapat, O; Ducot, B; Ponchon, T; Fritsch, J; Choury, A D; Pelletier, G; Buffet, C
Abstract : Background —Stenting is the treatment of choice for inoperable malignant strictures of the common bile duct. Criteria for the choice of stents (plastic versus metallic) remain controversial because predicting survival is difficult. Aims —To define prognostic factors in order to improve the cost effectiveness of endoscopic palliation. Patients —One hundred and one patients were included in a prospective trial. Seven prognostic variables for survival were analysed (age, sex, bilirubinaemia, weight loss, presence of liver metastases, and tumour histology and size). All patients were followed until death or at least one year after inclusion. By the end of the study, 81 (80.2%) patients had died. Results —In univariate analysis, the variables associated with survival were weight loss (p<0.05) and tumour size (p<0.01). By multivariate analysis, tumour size was the only independent prognostic factor (p<0.05). A threshold of 30 mm at diagnosis distinguished two survival profiles: the median survival of patients with a tumour greater than 30 mm was 3.2 months, whereas it was 6.6 months for patients with a tumour less than 30 mm (p<0.001). Conclusions —A practical strategy could be based on tumour size at diagnosis: a metal stent should be systematically chosen for patients with an inoperable tumour smaller than 30 mm, while larger tumours are efficiently palliated by a plastic stent.